The Education of Alice Hamilton : From Fort Wayne to Harvard. - Ringenberg, Matthew C. (Indiana University Press, 2019)
"As the founder of the Occupational Safety and Health Act and the first woman faculty member of Harvard University, Alice Hamilton will be remembered for her contributions to public health and her remarkable career. Born and raised in Fort Wayne, Indiana, Hamilton attended several medical schools reflecting her lifelong dedication to learning. Focusing on the investigation of the health and safety conditions -- or rather lack thereof -- in the nation's factories and mines during the second decade of the twentieth century, her discoveries led to factory and mine level-initiated reforms, and to city, state, and federal reform legislation. It also led to a greater recognition in the nation's universities for formal academic programs in industrial and public health. In 1919 the Harvard officials considered Hamilton the best qualified person in the country to lead their effort in this area. The Education of Alice Hamilton is an inspiring story of a woman dedicated to erudition and helping others" -- Provided by publisher.